Synthesis and Crystal Structure of 3-((m-Tolylamino)-methylene)-1,5-dioxaspiro[5.5]undecane-2,4-dione - Zeng, Wu-Lan; Liu, Hui-Lian (Asian Journal of Chemistry, 2014)
A new N,O-containing spiro compound 3-((m-tolylamino)methylene)-1,5-dioxaspiro[5.5]undecane-2,4-dione was synthesized and its crystal structure was determined by X-ray crystallographic techniques. The compound crystallizes in triclinic, space group P-1 with a = 7.0264 (14) Å, b = 7.8523 (16) Å, c = 14.102 (3) Å, a = 94.75 (3)º, b = 98.14 (3)º, g = 96.29 (3)º, C17H19NO4, Mr = 301.33, V = 761.7 (3) Å3, Z = 2, Dc = 1.314 g/cm3, F (000) = 320, μ(MoKa) = 0.094 mm-1, the final R = 0.0496 and wR = 0.3294. The 1,3-dioxane ring is in a distorted envelope conformation while cyclohexane ring assumes a highly symmetric chair conformation. There exist some intra- and intermolecular hydrogen bonds, C-H···p supramolecular interactions and p···p stacking interactions in the title compound. All above hydrogen bonds and intermolecular interactions play a significant role in stabilizing the crystal structures.